Identificación, formulación y evaluación de proyectos de nuevos productos de origen agrícola - Pinzón Catiblanco, Marco Antonio (Ingeniería, 1999)
The main aim of this paper is to discuss about the link between identification, formulation and evaluation as components of a process related with growth plantation new projects. Based on such study, it is possible to formulate a theoretical proposal to develop, in a near future, a method to correct different failures that we may find reading classic writers, which are in charge to cover and to treat concerning topics with industrial and agricultural projects. So, due to the dynamics of that kind of projects, it is necessary to give them a special treatment.